(3GdSjGSI GdLfGFjI ddeTQY GdbWQi ai ehGLgI ZSjd GdCehGd (B: s (3OQGSI ebGQfI (B/ s - (3CMeO Hf RGjO GdegfOi s; (3YeQ eMeO eMeO SGdes; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2015)
(3dbO GfJTQJ XGgQI ZSd GdGehGd ai GdeLJeYGJ GdZQHjI eY GfJTGQ hJTYH GdGfTWI GdGLQGejI cGdJLGQI ai GdeNOQGJ hGdJgQjH hGdQTGhi hGdYedGJ GdZjQ bGfhfjI hGdZT GdJLGQi hJRhjQ GdYedGJ hGdaSGO GdSjGSi hZjQgG ef GdLQGFe GdJi JJe HedjGQGJ GdOhdGQGJ hjfJL YfgG BKGQ GbJUGOjI hSjGSjI SdHjI hYdi GdQZe Ef XGgQI YSd GdGehGd bO GfJTQJ ai GdZQH GdG Gf GdbGFejf YdjgG OGFeG eG jJQHUhf HGdGShGb GdfGTFI hNGUI Gdi JSYi Gdi aJM GShGbgG GeGe QCS GdeGd GdGLfHi GdPi jJWdH OQGSI JTOjO GdSjGSI GdLfGFjI ai ehGLgI XGgQI ZSd GdGehGd ddMjdhdI Ohf GfJTGQGgG hJZdZdgG ai GdfTGW GdGbJUGOi ddOhd GdYQHjI s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2015s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B471-479s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdSjGSI GdLfGFjI s; (3GdeTQY GdbWQis; (3ZSjd GdCehGds; (3GdLQjeI GdefXeIs; (3GdELQGAGJ GdhbGFjIs; (3GdSQjI GdeUQajIs; (3GdGJaGbGJ GdOhdjIs; (3GdCMcGe GdLfGFjI GdGLfHjIs; (3GdSjGSI GdLfGFjI ddeTQY GdbWQjs; (3CQcGf LQjeI ZSjd GdCehGds; (3GdLQjeI GdCUdjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs